Comparative analysis of plastid genomes reveals rearrangements, repetitive sequence features, and phylogeny in the Annonaceae - Ping, Jingyao; Hao, Jing; Wang, Ting; Su, Yingjuan (Frontiers in Plant Science, 2024)
The Annonaceae stands as the most species rich family in the Magnoliales, a basal group of angiosperms. Widely distributed in tropical and subtropical regions, it holds significant ecological and economic value. The plastid genome (plastome) is often employed in studies related to plant phylogenetics, comparative genomics, evolutionary biology, and genetic engineering.Nonetheless, research progress on plastid genomics in the Annonaceae has been relatively slow. In this study, we analyzed the structure and repetitive sequence features of plastomes from 28 Annonaceae species. Among them, Mitrephora tomentosa and Desmos chinensis were newly sequenced, with sizes of 160,157 bp and 192,167 bp, and GC contents of 38.3% and 38.4%, respectively. The plastome size in the Annonaceae ranged from 158,837 bp to 202,703 bp, with inverted repeat (IR) region sizes ranging from 64,621 bp to 25,861 bp. Species exhibiting expansion in the IR region showed an increase in plastome size and gene number, frequent boundary changes, different expansion modes (bidirectional or unidirectional), and an increase in repetitive sequences. Specifically, a large number of dispersed repetitive sequences lead to an increase in the size of the LSC region in Goniothalamus tamirensis. Phylogenetic analysis revealed Annonoideae and Malmeoideae as monophyletic groups and sister clades, with Cananga odorata outside of them, followed by Anaxagorea javanica. This research uncovers the structural variation characteristics of plastomes in the Annonaceae, providing valuable information for understanding the phylogeny and plastome evolution of Annonaceae.